Hubungan Antara Status Penyakit Periodontal Dan Tingkat Pendidikan Pada Ibu Hamil Diwilayah Kerja Puskesmas Welahan Kabupaten Jepara Provinsi Jawa Tengah - Nugraha, Danny Setiawan; , drg. Edi Karyadi, MM, MDSc; , drg. Juwita Raditya Ningsih (2017)
Introduction: Pregnancy is a time that should be well pared. Maternal health must absolutely be maintained so that the fetus is healthy and not impaired orabnormalities.Inaddition to a balanced diet is also required thorough examination maternal health, including oral health examination. The state of pregnant women is one part of the objectives of health development in Indonesia. As one of the efforts in improving the health of pregnant women are pregnant women visit the K-4. Coverage of pregnant women visit the K-4 is the scope Pregnant women who have obtained in accordance with standard antenatal care at least four times in one work area at a certain time. But one of the diseases in pregnant women who need attention because the prevalence is still high is dental and oral diseases, particularly diseases of the periodontal tissues are gingivitis and periodontitis. Methods: This study used a test of Chi-Square Test Statistic (X2) with α 95% significance level (α = 0.05). The scale sed in this study is the ordinal scale.Result: the value of Chi Square test of significance between education level with assessed Periodontal Index (PDI) of 0.039 (p <0.05). This means that there is a relationship between perodontaldisease status and educational levels in pregnant women.Conclusion: There is a relationship between periodontal disease status and educational levels in pregnant women in PuskesmasWelahan Jepara regency.Keywords: ducationlevels,Periodontal,pregnant women, Chi-Square.